The The Influence of Transformational Leadership, Career Development, and Work Motivation on Employee OCB at PT Tanjung Priok Cirebon - Ayu Fatmawati; Nilla Agustin Rahayu (IJEBD (International Journal of Entrepreneurship and Business Development))
Objective: The aim of this study is to explore how work motivation, opportunities for career growth, and transformational leadership affect the organizational citizenship behavior (OCB) of employees at PT Tanjung Priok Cirebon.